Effect of interest rate on economic performance: evidence from Islamic and non-Islamic economies - Saba Mushtaq; Danish Ahmed Siddiqui (Financial Innovation, 2016)
Background: Saving and investment are two of the most important tools for economic growth. The interest rate has always been considered an important determinant of saving and investment. However, according to Islamic teachings, riba or earning interest on saving or investment is forbidden, and thus, many Muslims try to avoid earning income from the interest rate. Therefore, the aim of this study is to assess the effects of this religious guideline on the financial decisions of an Islamic country's population and its impact on saving and investment. Methods: We applied the random effect and system generalized method of moments (GMM) model separately to data of 17 non-Islamic and 17 Islamic countries from 2005 to 2013. Results: The results suggest that people in Islamic countries are not concerned about the interest rate on saving, but in non-Islamic countries, the interest rate, per capita income, and inflation have significant positive impacts, and national expenditure has a significant negative impact on saving. However, in Islamic countries, remittances received and national expenditure have negative significant impacts, and per capita income has a positive significant impact on saving. In the case of investment, interest rate and inflation show a negative effect on investment while trade affects investment positively in both Islamic and non-Islamic countries. Furthermore, domestic credit provided by banks has a negative significant effect on investment in non-Islamic countries, while in Islamic countries, remittances show a positive significant impact on investment. Conclusions: The governments and policy makers of Islamic countries should not imitate the economic policies of non-Islamic countries because religious factors play an important role in the interest rate-saving relationship. Instead, they should increase per capita income by improving employment conditions and by reducing remittances received and national expenditure. Policies on saving should not allow earning interest. Furthermore, in order to increase investment, efforts should be made to lower the interest rate and inflation, and to enhance remittances received and trade. These policies will increase saving and investment in Islamic countries, ultimately resulting in improved economic growth.
Keywords: E21; E22; E43; O11; Z13; 650; Interest rate; Economic performance; Islamic countries; Riba Saving; Investment